MENUJU TRANSFORMASI PENDIDIKAN: MODEL BAHAN AJAR BAHASA INDONESIA YANG IDEAL DAN PENUH KREATIVITAS - Andi St. Aisyah Dusreni; Aswini Febrianti; Abdul Haliq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article explores the importance of developing ideal and creative Indonesian language teaching materials in supporting educational transformation under the Merdeka Curriculum. The shift in learning paradigms requires teachers not only to deliver content but also to design relevant, contextual materials aligned with 21st-century skills. This study employs a qualitative descriptive approach to analyze various innovative teaching material models, including those based on technology, local wisdom, and modern learning theories. The findings indicate that creatively and adaptively designed materials significantly enhance student engagement and understanding. However, field implementation still faces challenges such as limited resources and low digital literacy among teachers. Therefore, continuous support for educators is essential to achieve meaningful educational transformation.